2020
DOI: 10.1097/md.0000000000022459
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study between blood cytokines and lymphocytes in early postoperative critical patients with compromised immune function

Abstract: Major surgery due to traumatic injury can activate early systemic postoperative pro-inflammatory responses and postoperative immunosuppression. However, the interaction between them is complex and not entirely clear. This study was performed in postoperative patients admitted to the intensive care unit (ICU) to elucidate the correlation between the systemic cellular immunity function and circulating cytokines levels in the early postoperative period. Twenty-four cases of postoperative patients admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The absolute level of peripheral blood lymphocytes, which are divided into T , B , and natural killer cells, is a critical immune function modulator 20,21 . Because B cells are mainly responsible for antibody production and T cells help to stimulate this process, 22,23 an increase in peripheral lymphocyte count is associated with immune dysfunction. A Japanese study reported that hypertriglyceridemia was associated with elevated lymphocyte counts in men but not in women 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The absolute level of peripheral blood lymphocytes, which are divided into T , B , and natural killer cells, is a critical immune function modulator 20,21 . Because B cells are mainly responsible for antibody production and T cells help to stimulate this process, 22,23 an increase in peripheral lymphocyte count is associated with immune dysfunction. A Japanese study reported that hypertriglyceridemia was associated with elevated lymphocyte counts in men but not in women 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sepsis caused by pathogenic infections, including bacteria and viruses, typically present lymphopenia (15,(33)(34)(35)(36), which can serve as a biomarker for immunosuppression (37,38). In addition, a continuous and sustained decrease in total circulating lymphocytes is closely associated with disease aggravation and death in septic patients (33,39).…”
Section: Discussionmentioning
confidence: 99%
“…Albumin preconditioning could abrogate the lipopolysaccharides (LPS)mediated increase in the protein levels of tumor necrosis factor alpha (TNF-α) in cultured macrophages and septic mice (44). Due to the negative correlation between hyperinflammation and systemic immune function (38,45,46), hyperinflammation mediated by reduced levels of albumin in the poor sleep group would also compromise the immune function. ANP, a cardiovascular hormone mainly secreted by the heart atria (47), plays important protective roles in many diseases, including ventricular hypertrophy, myocardial injury, atherosclerosis, hypertension, tumor, acute lung injury, ischemia/reperfusion injury, and sepsis (48,49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations